Evaluating the Impact of Sister City Cooperation between Bandung and Kawasaki on Environmental Sustainability - Sabati, Cholifatul Latifah (Journal of Paradiplomacy and City Networks, 2024)
This research provided an in-depth analysis of the role of paradiplomacy practiced by the Government of South Sulawesi Province in enhancing agricultural exports to Egypt. The study utilized a conceptual framework integrating Paradiplomacy and International Trade, focusing on the impact of paradiplomacy policies on export volumes. The methodology was rooted in descriptive research, aiming to depict the findings clearly and comprehensively. Results indicated that the Government of South Sulawesi Province engages in the form of paradiplomacy termed global paradiplomacy, acting as a facilitator in international trade. Effective strategies for promoting exports included personal selling, public relations through webinars and training sessions, and participation in trade exhibitions. The research highlighted the crucial role of regional governments in boosting agricultural export volumes, supported by efforts in infrastructure development and service improvements. The application of global paradiplomacy enabled the Government of South Sulawesi Province to autonomously establish trade relations and expand market access to Egypt, leading to a significant increase in agricultural exports. This study offered a comprehensive overview of how paradiplomacy practices can positively impact regional agricultural exports, emphasizing the successful export promotion strategies and their outcomes. The findings demonstrated the effectiveness of paradiplomacy in fostering regional economic growth through international trade expansion.